Change in Myoglobin Denaturation Among Three Degrees of Doneness of Three Muscles - E. S. Beyer; K. J. Farmer; E. G. Kidwell; S. G. Davis; K. M. Harr; K. R. Lybarger; L. A. Egger; M. D. Chao; M. D. Zumbaugh; J. L. Vipham; M. C. Hunt; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to determine the changes in myoglobin denaturation through cooking three different muscles to medium rare, medium, or well-done degrees of doneness. Study Description:Strip loins (n= 12) and top butts (n= 12) were used to evaluate the physiochemical properties of thelongissimus dorsi, biceps femoris,andgluteus mediusfor three degrees of doneness (DOD; medium rare, medium, and well-done). The Bottom Line:As expected, the myoglobin denaturation percentage increased with increasing DOD and behaved similarly to changes in the a* values. This research gives more insight into the impacts of cooking and the changes that proteins, especially myoglobin, undergo between different DOD.
Keywords: degrees of doneness; cooked color; myoglobin